Hubungan Dominansi Pohon dengan Temperature Humidity Index (Thi) Di Hutan Kota Babakan Siliwangi Bandung Jawa Barat - Raizal Fahmi Solihat; Muhamad Elvan Nurfajri (Fakultas Kehutanan Universitas Winaya Mukti, 2018)
Physical development in the city of Bandung which is increasing causes a decrease in green open space. Babakan Siliwangi Bandung City Forest is one of the green open spaces so it is necessary to know the correlation between tree dominance and the Temperature Humidity Index (THI) value in the formation of micro climates. The object research is to determine the relationship between tree dominance and THI. The method by vegetation analysed, measuring temperature and humidity. The results of research are: 1) Comfort index (THI) in the Babakan Siliwangi City Forest Park in Bandung in August 2017 is relatively comfortable <26 THI. 2) The correlation value of tree dominance with THI is -0.14 which means that there is no relationship between the dominance value and THI. Keywords : Tree, Forest urban, THI, Bandung